Physical aspects of care : pain and gastrointestinal symptoms - Paice, Judith A. (HPNA palliative nursing manuals ;, 2015)
Palliative care is an essential element of our health care system and becoming increasingly significant amidst an aging society and organizations struggling to provide both compassionate and cost effective care. Palliative care is also characterized by a strong interdisciplinary approach. Nurses are at the center of the palliative care team across settings and populations. The second volume in the HPNA Palliative Nursing Series, Physical Aspects of Care: Pain, Nausea and Vomiting, Fatigue and Bowel Management, provides an overview of the principles of symptom assessment and management for symptoms, including pain, fatigue, nausea and vomiting, constipation, diarrhea, obstruction, and ascites.